Deterring illegal smartphone use while driving: Are perceptions of risk information associated with the impact of informal sanctions?. (April 2022) - Kaviani, F.; Young, K.L.; Koppel, S.
Highlights: Despite acknowledgement of peer disapproval, 18-25y/o's engaged device illegally. Hurting others greatest worry, especially for occasional illegal smartphone users. 70% of drivers unfamiliar with number of deaths and injuries caused by distraction. Effectiveness of risk information associated with impact of informal sanction. Explore associating illegal smartphone use with alcohol/cannabis impaired driving. Abstract: Advertising campaigns have used threat appeals to increase the perceptions of risk associated with dangerous driving behaviours. Building on recent research that suggests increasing the pertinence of informal sanctions (sense of guilt, fear of peer disapproval, or fear of hurting oneself and others) decreases the likelihood of illegal smartphone engagement while driving, this study aimed to determine if perceptions of risk information, that is, how effective drivers believe the information is in deterring their illegal use, is associated with perceptions of informal sanctions. An online survey of 1027 Victorians who self-reported illegal smartphone use while driving asked participants to rate the personal deterrent effectiveness of five types of risks associated with illegal smartphone use while driving. A hierarchical linear regression model explored the associations between the most effective risks and each informal sanction. Female drivers were more likely than male drivers to experience guilt, fear of social loss and fear of physical loss when using their smartphones illegally. More frequent illegal smartphone engagement while driving was associated with decreased impact of informal sanctions. Female drivers were more likely than male drivers to perceive each risk as effective. The most effective piece of information was, " Contributes to 16% of Victorian road deaths and serious injuries annually "; it was also the least known (32.7% males, 26.7% females). This message, alongside, " Increases risk of a crash comparable to those associated with driving under the influence of alcohol or cannabis" and, " A 2 s glance at your phone while driving at 50 km/h effectively means driving blind for 27 m", were associated with stronger perceptions of guilt, fear of peer disapproval, or fear of hurting oneself and others when thinking about using a smartphone illegally while driving. These results suggest tailoring and targeting these specific risk information may be effective in deterring illegal smartphone use while driving.